2021
DOI: 10.1016/j.neures.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transcranial direct current stimulation on corticospinal and cortico-cortical excitability and response variability: Conventional versus high-definition montages

Abstract: Response variability following transcranial direct current stimulation (tDCS) highlights need for exploring different tDCS electrode montages. This study compared corticospinal excitability (CSE), cortico-cortical excitability and intra-individual variability following conventional and HD anodal (a-tDCS) and cathodal (c-tDCS) tDCS. Fifteen healthy young males attended four sessions at least one-week apart: conventional a-tDCS, conventional c-tDCS, HD-a-tDCS, HD-c-tDCS. TDCS was administered (1mA, 10-minutes) o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…The results of this current study were only reported on a specific subgroup of the population and via one tDCS electrode configuration and dosage. Recruiting just healthy young males for this study was an attempt to minimize potential participant factors as sources of inter‐individual variability (Pellegrini et al., 2020). Therefore, whether these current results can be extrapolated to other populations remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this current study were only reported on a specific subgroup of the population and via one tDCS electrode configuration and dosage. Recruiting just healthy young males for this study was an attempt to minimize potential participant factors as sources of inter‐individual variability (Pellegrini et al., 2020). Therefore, whether these current results can be extrapolated to other populations remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty‐one healthy male volunteers aged (mean ± SD ) 26.82 ± 7.62 years provided written informed consent to attend two experimental sessions. Sample‐size was calculated (with 80% power) based on results of a pilot conducted on 15 subjects (Pellegrini et al., 2020). In this pilot study, changes in CSE following a‐tDCS were reported with a Cohen's d moderate effect size of 0.45 (Pellegrini et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the variance in experimental outcomes in response to tDCS was caused by several factors associated with high inter-individual variability, including the organization of local circuits, basal level of function, psychological state, level of neurotransmitters and receptor sensibility, baseline neurophysiological state, and genetic aspects (López-Alonso et al, 2015;Pellegrini et al, 2018a,b;. In addition, those previous studies used different experimental designs and stimulation protocols (i.e., different montages), potentially contributing to the variance in the results or even the reversal effect (Datta et al, 2009;Angius et al, 2018;Hassanzahraee et al, 2020;Pellegrini et al, 2020). For example, Hassanzahraee et al (2020) observed the reversal of corticospinal excitability of anodal tDCS with a current intensity of 1.0 mA when the stimulation duration was over 26 min, which may provide certain implications for preventing excessive brain activation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the charge accumulation at the electrode/electrolyte interface, these inert electrodes cannot deliver high current density. Therefore, the area of inert electrodes has to be quite large (25~35 cm 2 ), which severely sacrifices the spatial resolution of tDCS [ 33 , 34 , 35 ]. In general, the current density of inert electrodes is less than 0.08 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%